2020
DOI: 10.1186/s12929-020-00672-9
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning-based segmentation of ischemic penumbra by using diffusion tensor metrics in a rat model

Abstract: Background: Recent trials have shown promise in intra-arterial thrombectomy after the first 6-24 h of stroke onset. Quick and precise identification of the salvageable tissue is essential for successful stroke management. In this study, we examined the feasibility of machine learning (ML) approaches for differentiating the ischemic penumbra (IP) from the infarct core (IC) by using diffusion tensor imaging (DTI)-derived metrics. Methods: Fourteen male rats subjected to permanent middle cerebral artery occlusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Similarly, we previously reported that the combination of DTI metrics and ML can effectively identify the penumbra without the need for contrast agents [38]. In the present study, we adopted a stack-based ensemble technique, substantially increasing the Pearson correlation coefficient between the ML-estimated PV and the PDM-defined PV from 0.61 [38] to our value of 0.93. Despite its optimal performance, this ensemble technique requires extended training time and high computational resources [39].…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Similarly, we previously reported that the combination of DTI metrics and ML can effectively identify the penumbra without the need for contrast agents [38]. In the present study, we adopted a stack-based ensemble technique, substantially increasing the Pearson correlation coefficient between the ML-estimated PV and the PDM-defined PV from 0.61 [38] to our value of 0.93. Despite its optimal performance, this ensemble technique requires extended training time and high computational resources [39].…”
Section: Discussionmentioning
confidence: 73%
“…Despite FA being extensively examined as a potential diagnostic biomarker among DTI-derived metrics, its performance in the hyperacute phase remains controversial because of its definition as a ratio of q to L [59,60]. The increase, reduction, or no change in FA values is dependent on the simultaneous analysis of q and L. However, studies have consistently reported decreased MD values [8,38,60], which is reflected in our importance permutation results. MD, p, and L reflect the magnitudes of molecular motion of water, which changes and becomes detectable within minutes after stroke onset.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Stroke has been ranked as a primary cause of disability and death in the elderly populace worldwide [ 1 ] and in the early phases of ischemic stroke, severe cell death and mitochondrial dysfunction may result in long-term neurological impairment [ 2 ]. As a countermeasure, vascular recanalization is currently the most efficacious treatment for acute ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%